Solvothermal synthesis of CdS nanorods using hydroxyethyl cellulose as a template - Thongtem T. (2014)
CdS nanorods were solvothermally produced from Cd(CH3COO)2 and S powder using ethylenediamine (en) as a solvent and hydroxyethyl cellulose (HEC) as a template. The phase with hexagonal structure was detected using XRD and SAED, which is in perfect accordance with the results obtained by simulation. SEM, TEM and HRTEM revealed the development of nanorods with a number of atoms arranged in crystal lattices. When the appropriate amount of HEC was used, the longest nanorods, with preferential growth in the [0 0 1] direction, were produced. Raman spectra showed the fundamental and overtone modes at the same wavenumbers of 301 and 599 cm-1, respectively. Their relative intensities at each temperature were strongly influenced by the anisotropic geometry of the products. Photoluminescence caused by electron-hole recombination was detected at 470 nm, and by surface trapping induced emission at 575 nm. The formation mechanism of CdS nanorods was also proposed based on the experimental results. © 2009 Elsevier B.V. All rights reserved.